Multi-Sensor Digital X-Ray Receivers - Miroshnichenko, S.I.; Nevgasimiy, A.A. (Science and Innovation, 2024)
The multi-sensor structures have been successfully used in manufacture of digital receivers. A lot of sensors forming the partial image allowed the researchers to obtain the optimal parameters of radiographic, mammographic, and fluoroscopic receivers. The paper deals with analysis of multi-sensor structure properties, substantiation of options of their implementation, and noise attenuation in X-ray receivers.